Blepharocheilodontic (BCD) syndrome: Expanding the phenotype? - Lopes, Vera Lúcia Gil da Silva; Guion-Almeida, Maria Leine; Rodini, Elaine Sbroggio de Oliveira [UNESP] (Wiley, 2003)
We describe affected individuals in three generations of a family and another sporadic case, all Brazilian patients, with a combination of signs that diagnose the BCD syndrome. In addition to the cardinal signs, the sporadic case has hypothyroidism and imperforate anus, which was observed previously in one patient. The broadened phenotype and the possibility of involvement of p63 and IRF6 genes in this condition are discussed. © 2003 Wiley-Liss, Inc.
Keywords: Ankyloblepharon; Anus; Autosomal dominant inheritance; Cleft lip/palate; Ectodermal dysplasia; Imperforate; IRF6 gene; P63 gene; interferon; interferon regulatory factor 6; protein p53; unclassified drug; anus atresia; blepharocheilodontic syndrome; clinical examination; clinical feature; disease course; familial disease; family history; gestation period; hypothyroidism; mental development; motor development; phenotype; physical examination; preschool child; priority journal; Blepharophimosis; Cleft Lip; Cleft Palate; Diagnosis, Differential; DNA-Binding Proteins; Family Health; Hypothyroidism; Interferon Regulatory Factors; Membrane Proteins; Phenotype; Phosphoproteins; Syndrome; Tooth Abnormalities; Trans-Activators; Transcription Factors; Tumor Suppressor Proteins